Social Media Expression, Political Extremity, and Reduced Network Interaction: An Imagined Audience Approach. (January 2022) - Su, Min-Hsin; Suk, Jiyoun; Rojas, Hernando
The recent rise of political extremity and radicalization has presented unique challenges to contemporary politics, governance, and social cohesion in many societies in the world. In this study, we propose an imagined audience approach to understand how social media's expanded expression capabilities are related to users' political extremity and reduced network interaction. We demonstrate the usefulness of our imagined audience framework using a multi-country survey data set. Results from the United States, South Korea, and Japan reveal that expressive use of social media is associated with more extreme political attitudes and heightened intolerance, but the effect is contingent on whom the expresser has in mind as their audience. In particular, expressing one's political self has a depolarizing effect for those expecting low audience reinforcement. We test the boundary conditions of our model in a more restricted information environment with a Chinese sample. We conclude by discussing the significance of our imagined audience approach and its relevance to today's technology-mediated self-presentation.